Bronchial responsiveness to methacholine and adenosine 5′-monophosphate in atopic and non-atopic preschool children with recurrent wheezing - Kim, D. K.; Choi, S. H.; Yu, J.; Yoo, Y.; Koh, Y. Y. (Clinical and experimental allergy, 2007)
Summary Background It is well known that atopy is a major determinant of bronchial hyper‐responsiveness (BHR) in both asymptomatic and asthmatic children. However, the relationship between atopy and BHR has not been well studied in preschool children with wheezing. BHR is usually measured by bronchial challenges using direct and indirect stimuli. Objective The aim of this study was to investigate whether atopic and non‐atopic preschool wheezers display similar or different BHR profiles for direct and indirect stimuli. Methods Methacholine and adenosine 5′‐monophosphate (AMP) bronchial challenges were performed in 4 to 6‐year‐old children with recurrent wheezing, using a modified auscultation method. The end‐point was defined as the appearance of wheezing and/or oxygen desaturation. Atopy was determined to be present when a child had at least one positive reaction to a panel of 13 common airborne allergens in the presence of positive and negative controls. Results A positive response to methacholine (an end‐point concentration 8 mg/mL) was observed in 89.3% (50/56) of atopic wheezers and in 83.8% (31/37) of non‐atopic wheezers (P=0.44) for the difference. By contrast, the frequency of a positive response to AMP (an end‐point concentration 200 mg/mL) was significantly higher in the atopic group (47/56, 83.9%) compared with the non‐atopic group (12/37, 32.4%; P<0.01). Conclusion While a majority of both atopic and non‐atopic preschool wheezers were hyper‐responsive to methacholine, atopic subjects were more hyper‐responsive to AMP than non‐atopic subjects. These findings suggest that atopic and non‐atopic wheeze in preschool children are related to distinctive pathophysiologic pathways.